Pelatihan Pembuatan Permen Jelly dari Teh Matcha sebagai Pengendali Kadar Gula Darah di Kelurahan Kalisegoro Semarang: Training on Making Jelly Candy from Matcha Tea to Control Blood Sugar Levels in Kalisegoro Village, Semarang - Anwar, Khoirul; Puspitasari, Anita Dwi; Maharani, Farikha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Diabetes is a chronic disease with increasing prevalence and is becoming a global health threat. One plant that is efficacious for lowering blood sugar levels is matcha tea which can be made into a processed product in the form of jelly candy. This community service aims to increase understanding and train the community to make jelly candy food products from matcha which comes from agricultural products for complementary therapy for diabetes mellitus. This community service was carried out in Kalisegoro Village. The participants in this service activity were 25 PKK women and was carried out in three stages. The first stage will be a meeting and coordination with the village head and the PKK women's group who will conduct training in making jelly candy. The second stage is the activity of preparing material and preparing practical methods. The third stage, namely coaching and training, includes providing material to training participants by theory and demonstrations. The results of this community service found that 20 people out of 25 participants could answer pretest questions related to the causes of disease and natural treatment for diabetes mellitus. The results of the jelly candy-making tutorial showed that as many as 20 participants could answer post-test questions and understand how to make the product. Based on the results of oral questions and answers, it was found that as many as 15 participants were interested in continuing the results of their service by making their food at home and using it as a family dinner.